ANALISIS PERILAKU KONSUMEN DALAM PEMBELIAN LEDRE (STUDI KASUS DI TOKO MORO SENENG DESA PADANGAN DAN TOKO DADI TRESNO KOTA BOJONEGORO) - AHMAD FANANI; TAUFIK R D A NUGROHO; AMINAH H MONINTHOFA (Universitas Sebelas Maret, 2013)
The consumer behavior analysis in the purchase of a product is influenced by the attributes attached to the product. This study aimed to describe the consumer’s characteristics and analyze the attributes that influence consumers in buying ledre. The research was conducted in two places, Toko Moro Seneng at Padangan Village and Toko Dadi Tresno at Bojonegoro City. The sampling method was done by using accidental sampling, with 30 respondents. The data analysis used descriptive and conjoint analysis.